2000
DOI: 10.1111/j.1553-2712.2000.tb02103.x
|View full text |Cite
|
Sign up to set email alerts
|

The Clinical Utility of Serologic Markers in the Evaluation of the Acute Scrotum

Abstract: Abstract. Objective: To examine the presence of interleukin-1 (IL-1), interleukin-6 (IL-6), and creatine phosphokinase-MM (CPK-MM) in patients with acute scrotal pain and assess their clinical utility in the diagnosis of testicular torsion (TT) and epididymitis. Methods: Twenty-five patients with acute scrotal pain were prospectively enrolled over a two-year period. History, physical examination, complete blood count, urinalysis, and scrotal ultrasound were performed. Testicular torsion was confirmed by surgic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 12 publications
0
10
0
1
Order By: Relevance
“…Apart from clinical features, various serologic markers and acute-phase proteins have also been reported as complementary diagnostic tools to exclude TT. According to these studies, C-reactive protein and interleukin-6 were significantly elevated in EO as compared with TT (5,19).…”
Section: Discussionmentioning
confidence: 92%
“…Apart from clinical features, various serologic markers and acute-phase proteins have also been reported as complementary diagnostic tools to exclude TT. According to these studies, C-reactive protein and interleukin-6 were significantly elevated in EO as compared with TT (5,19).…”
Section: Discussionmentioning
confidence: 92%
“…It has been reported that CK and its isoenzymes have a diagnostic value in tissue ischaemia, especially in testicular torsion 2,6,27 . Serum CK levels in rats in the early period following spermatic cord torsion increased significantly before necrosis of the testicular tissue 6 .…”
Section: Discussionmentioning
confidence: 98%
“…The next step is the introduction of scintigraphy, which is much more sensitive in detecting TT than US examination, with a sensitivity of close to 100%. [3,9,41,42] Unfortunately, the study is time-consuming, uses ionizing radiation, and not always available. Rivers et al, [3] recommending the determination of levels of interleukin 6 in the differentiation of epididymitis from TT, indicates the need for the development of laboratory diagnostics.…”
Section: All Above Authorsmentioning
confidence: 99%